Ventricular septal rupture, right ventricular dissection, and tricuspid chordae rupture—A rare complication after inferior and right ventricular infarction. Issue 8 (8th September 2014) - Li, Xiao‐hong; Zhao, Ying; Dong, Jianzeng; He, Yihua; Liu, Wenxu; Han, Jiancheng
ABSTRACT A 76‐year‐old man under stable hemodynamic condition was admitted to our hospital for delayed percutaneous coronary intervention following a diagnosis of acute inferior myocardial infarction. Bedside echocardiography revealed ventricular septal rupture at the basal posteroinferior wall with a large left‐to‐right shunt. Right ventricular free‐wall intramyocardial dissection and tricuspid chordae rupture were noted. Coronary angiography demonstrated occlusion of the proximal right coronary artery, which was treated by balloon angioplasty and stenting. While preparing for surgical repair, the patient's overall cardiac and renal function deteriorated and surgery was contraindicated. The patient died 16 days after discharge. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound 43:512–515 2015